The Level of Instagram's Influence on Millennials' Education Towards the Golden Generation - Besta Gulo; Muhammad Dhafa; M Arif Ridwan; Supina Batubara (Journal of Information Technology, computer science and Electrical Engineering, 2024)
In this digital era, Instagram has become one of the most popular social media platforms among millennials. This article investigates the influence of Instagram as a tool to improve education and learning among millennials, with a focus on efforts towards creating a "Golden Generation". This study uses qualitative methods by collecting data from interviews and observations of active Instagram users. The findings show that Instagram not only influences the lifestyle and mindset of millennials, but also plays an important role in educating them through the widespread educational content on the platform. The implications of this research underscore the importance of utilizing social media in a positive way to improve education and prepare millennials to become a skilled and knowledgeable generation.